Evaluasi terhadap Elemen Implementasi dalam Sistem Manajemen Keselamatan Pertambangan pada Tambang Terbuka PT. Rolas Nusantara Tambang Kabupaten Pasuruan Provinsi Jawa Timur - Adipratama Winanta, Kevin; Supandi,; Mustapa Ali Mohamad, (ReTII, 2023)
PT. Rolas Nusantara Tambang is an andesite commodity mining company located in Desa Ambal Ambil, Kejayan District, Pasuruan Regency, East Java. In terms of the implementation of andesite rock mining at PT. Rolas Nusantara Tambang is certainly inseparable from the potential for workplace accidents that could occur due to human factors and environmental factors. To prevent and overcome these problems, it is necessary to conduct research and evaluation of implementation elements in the mining safety management system (SMKP) in this company so as to minimize losses and work accidents that occur. Assessment and evaluation of the implementation of SMKP Minerba are assessed based on the assessment criteria in the Decree of the Director General of Minerals and Coal, Ministry of Energy and Mineral Resources No.185.K/37.04/DJB/2019. Implementation of SMKP Minerba Implementation Elements at PT. Rolas Nusantara Tambang only obtained a total element value of 35 out of a total of 121 sub-element values ​​so the percentage for the SMKP Minerba implementation element obtained was 10%. It can be seen that the percentage obtained is quite far from the set value, so improvements and increases in the value of the element and sub-element weights need to be continuously improved in order to obtain a standardized value. Keywords: Evaluation, Implementation Element, SMKP Minerba, Percentage, Value.